Problems from Kant - Van Cleve, James (OUP E-Books., 1999)
This examination of Kant's "Critique of Pure Reason" provides an analysis of the metaphysical and epistemological questions of Kant's work. It presents clear and detailed discussions of Kant's arguments on these themes, as well as critical assessments of Kant's reasoning and conclusions.